The ethics of unlinked anonymous testing of blood: views from in-depth interviews with key informants in four countries. Issue 6 (20th December 2012) - Kessel, Anthony S; Datta, Jessica; Wellings, Kaye; Perman, Sarah
Abstract : Objectives: In this study we explore the ethical issues around unlinked anonymous testing (UAT) of blood, a method of seroprevalence surveillance for infectious diseases. Our study focused on UAT for HIV, although UAT can be used for other infectious diseases. The objectives of the research were to gain a better understanding of the views of key informants in countries adopting different UAT testing strategies, and to use the findings of the research to inform health policy. Design: Qualitative study using in-depth interviews and ethical analysis. Setting: Four countries using different strategies around UAT of blood for HIV (the UK, the USA, the Netherlands and Norway). Participants: Twenty-three key informants in the four countries. Results: Participants from the four countries have different views on UAT of blood, and the approaches and policies on UAT adopted by different countries have been historically and culturally determined. We use our findings to explore the relationship between public health policy and ethics, framing our discussion in relation to two important contemporary debates: informed consent for participation in medical and public health research; and the balance between the individual good and the public good. Conclusions: Qualitative research and ethical analysis of UAT of blood in different countries has yielded important findings for consideration by policy makers. The policy of UAT of blood for HIV and other diseases in the UK needs reconsideration in the light of these findings.